Pesquisa de espécies de vibrio spp. Isolados de produtos de origem animal clandestinos e efluentes hídricos do norte do Tocantins - Rodrigues, Yron Moreira (2024)
Bacteria of the genus Vibrio spp. are common causes of gastroenteritis associated with the consumption of seafood. These pathogens are waterborne and can be transmitted by food, but there are few estimates of them and cases of infection are underdiagnosed. Vibrio cholerae, V. parahaemolyticus and V. vulnificus are the main species associated with infections in humans. Recent studies have focused on potential environmental factors and reservoirs, however, as they are important risk factors for humans, as agents of disease transmission, especially through food, it is essential to monitor their presence in food. The aim of this study was to verify the specificity of a biomolecular assay for species of Vibrio cholerae, V. parahaemolyticus and V. vulnificus; isolate suggestive bacteria and confirm the morphological identification suggestive of the species; verify the specificity of a biomolecular PCR assay and determine whether the assay is sufficient for the detection of pathogenic species of Vibrio spp. in clandestine animal products and water effluent samples from the Lontra River in Araguaína, Tocantins. 565 isolates suggestive of Vibrio spp. were evaluated, of which 103 isolates were confirmed using PCR-Uniplex methodology for Vibrio spp. species and, among these, 10 isolates were selected for genetic sequencing of the 16S rRNA gene. The sequencing results confirmed Aeromonas spp., Escherichia coli and Morganella spp. as species for the isolates used. Under the conditions performed, it was not possible to establish the specificity of the PCR-Uniplex and PCR-Multiplex techniques that were capable of determining the species of Vibrio spp. studied. Therefore, other methodological approaches or changes to the protocols described in the literature should be validated for research into pathogenic microorganisms of this genus.